Recording Data of Patients with Alcohol Use Disorders in Mar del Plata, Argentina - Conde, Karina; Remaggi, Milena Laura; Peltzer, Raquel Inés; Lichtenberguer, Aldana; Cremonte, María (Pensando Psicología, 2016)
Introduction: Data recorded on alcohol consumption are important for the diagnosis and prognosis of alcohol use disorders.Objective: This descriptive study aimed to characterize references to alcohol consumption and other related variables in hospital records of patients treated in a specialized alcoholism unit at a public hospital in Mar del Plata, Argentina.Methodology: Records of 60 admissions between February and November 2011 were examined and categorized by extracting data related to alcohol consumption, source of referral, diagnosis, treatment, hospitalization, and other diseases, as well as aspects of family and socioeconomic environment. Subsequently, a descriptive analysis was conducted considering the percentage of records mentioning these aspects.Results: While the recording of data regarding alcohol consumption was high, it was generally incomplete. Recorded data made evident that the bio-psycho-social conditions of these patients are unfavorable for successful treatment.Conclusions: The need to systematize information (for example, through unified medical records) and ways to prevent progression of alcohol use disorders are discussed.
Keywords: Argentina; hospital care; records; alcohol use disorder